POSTRZEGANIE ZWYCZAJÓW ODNOSZĄCYCH SIĘ DO OBOWIĄZKU ZACHOWANIA POUFNOŚCI W ARBITRAŻU. ANALIZA WYNIKÓW ANKIETY PRZEPROWADZONEJ PRZEZ SĄD ARBITRAŻOWY LEWIATAN WŚRÓD POLSKICH PRAKTYKÓW ARBITRAŻOWYCH - Gessel-Kalinowska vel Kalisz, Beata (Zeszyty Prawnicze, 2016)
THE PERCEPTION OF THE PRACTICE OF CONFIDENTIALITY IN ARBITRATION. AN ANALYSIS OF THE RESULTS OF A SURVEY CARRIED OUT BY THE LEWIATAN COURT OF ARBITRATION AMONG POLISH ARBITRATION PRACTITIONERS Summary As with numerous other systems of law, such as Norwegian, Swedish or Australian law, the Polish legal system does not have a clear and uniform norm of law governing confidentiality and privacy in arbitration. Public opinion frequently refers to the role of custom as the source of the obligation to preserve confidentiality, although usually it does so without a detailed analysis of the subject and object of this obligation. This fact provided the inspiration for a survey carried out among Polish arbitration practitioners. The results of the survey present an interesting picture of what is subjectively perceived by arbitration practitioners as forming part of the confidentiality canons in arbitration proceedings. In principle, they reflect the worldwide trends, i.e. as far as the object of the confidentiality obligation is concerned – in camera sessions and the confidentiality of awards, and as regards its subject – the confidentiality obligation imposed on arbitrators and arbitration institutions. In addition, the customary practice of keeping confidential any information obtained in the course of proceedings is perceived as the right conduct as far as the object of the obligation is concerned. One of the very controversial issues is the matter of parties’ responsibilities, which leads to further questions as to individual arbitrators’ membership of the social (professional) group known as “arbitration practitioners”.